Influence of Low-Temperature Phase Transitions on Erythrocytes Integrity - Ulizko, Pavlo Yu.; Bobrova, Olena M.; Vodopyanova, Larisa A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 179.